2004
DOI: 10.2209/tdcpublication.45.19
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Analysis of Foods for Infants and Estimation of Daily Fluoride Intake

Abstract: The mean daily fluoride intake in infants was estimated on the basis of their intake of commercial foods for infants in Japan and evaluated in order to establish the effectiveness and safety criteria for water fluoridation, which is practiced as a preventive measure for dental caries suitable in life stages from children to the elderly. Based upon the intakes of foods for infants, the mean daily fluoride intake was estimated to be 0.166 mg in infants aged 3-4 months, 0.202 mg in those aged 5-6 months, and 0.26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
2
15
4
Order By: Relevance
“…In reference to the AI and UL of other regions, since the AI and UL have not been established in Japan, the results of this study suggested that the F intake of infants in Japan was unlikely to exceed the UL or reach even the AI. This supports the results of previous studies which have reported that F intake from solid foods and beverages in Japanese children aged 3 months to 8 years were less than 0.05 mg F/kg bw/day [Nishijima et al, 1993;Kimura et al, 2001;Murakami et al, 2002;Tomori et al, 2004;Nohno et al, 2006], and indicates that the F intake of infants at, and after, weaning age is unlikely to exceed the AI.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In reference to the AI and UL of other regions, since the AI and UL have not been established in Japan, the results of this study suggested that the F intake of infants in Japan was unlikely to exceed the UL or reach even the AI. This supports the results of previous studies which have reported that F intake from solid foods and beverages in Japanese children aged 3 months to 8 years were less than 0.05 mg F/kg bw/day [Nishijima et al, 1993;Kimura et al, 2001;Murakami et al, 2002;Tomori et al, 2004;Nohno et al, 2006], and indicates that the F intake of infants at, and after, weaning age is unlikely to exceed the AI.…”
Section: Discussionsupporting
confidence: 91%
“…Lactose-free milk is for infants with lactose intolerance. Two previous studies on measuring IMF in Japan reported the F content of powdered unreconstituted products to be 0.53-1.33 g/g [Nishijima et al, 1993] and 0.30-1.00 g/g [Tomori et al, 2004]. The products measured in these two reports were almost similar, but the present study included only one similar product to those measured previously.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…More recently, Tomori et al. (32) analysed 68 samples of commercial infant foods and drinks in Japan, 19 (16 foods, three drinks) of which were RTF products. Of these ‘retort‐packed’ products, the F concentrations ranged from 0.14 to 0.18 μg/g for fruit juices, 0.04–0.56 μg/g for vegetables, 0.02–0.18 μg/g for meat & fish and 0.06–0.44 μg/g for cereals.…”
Section: Rtf Infant Foodsmentioning
confidence: 99%